Question and Answers Forum

All Questions      Topic List

Limits Questions

Previous in All Question      Next in All Question      

Previous in Limits      Next in Limits      

Question Number 169711 by mnjuly1970 last updated on 06/May/22

      prove that:        lim_( x → 0) ( (1/x^( 2) )  − (e^( x) /((e^( x) −1 )^( 2) )) ) = (1/(12))

provethat:limx0(1x2ex(ex1)2)=112

Commented by infinityaction last updated on 06/May/22

i think question is wrong

ithinkquestioniswrong

Commented by cortano1 last updated on 07/May/22

no. the question right

no.thequestionright

Commented by infinityaction last updated on 07/May/22

thank you sir   got my mistake

thankyousirgotmymistake

Answered by qaz last updated on 07/May/22

L=lim_(x→0) ((1/x^2 )−(e^x /((e^x −1)^2 )))=lim_(x→0) ((e^(2x) −2e^x +1−x^2 e^x )/x^4 )  e^(2x) −2e^x +1−x^2 e^x   =(1+2x+(1/2)(2x)^2 +(1/6)(2x)^3 +(1/(24))(2x)^4 +...)−2(1+x+(1/2)x^2 +(1/6)x^3 +(1/(24))x^4 +...)+  1−x^2 (1+x+(1/2)x^2 +...)  =(((16)/(24))−(2/(24))−(1/2))x^4 +...=(1/(12))x^4 +o(x^4 )  ⇒L=lim_(x→0) (((1/(12))x^4 +o(x^4 ))/x^4 )=(1/(12))

L=limx0(1x2ex(ex1)2)=limx0e2x2ex+1x2exx4e2x2ex+1x2ex=(1+2x+12(2x)2+16(2x)3+124(2x)4+...)2(1+x+12x2+16x3+124x4+...)+1x2(1+x+12x2+...)=(162422412)x4+...=112x4+o(x4)L=limx0112x4+o(x4)x4=112

Answered by cortano1 last updated on 07/May/22

 lim_(x→0)  (((e^x −1)^2 −x^2 e^x )/(x^2 (e^x −1)^2 ))    = lim_(x→0)  (((1+x+(x^2 /2)+(x^3 /6)+O(x^3 )−1)^2 −x^2 (1+x+(1/2)x^2 +(1/6)x^3 +O(x^3 )))/(x^2 (1+x+(1/2)x^2 +(1/6)x^3 +O(x^3 )−1)^2 ))   = lim_(x→0)  ((x+(1/2)x^2 +(1/6)x^3 +...−(x^2 +x^3 +(1/2)x^4 +(1/6)x^5 +...))/(x^2 (x+(1/2)x^2 +(1/6)x^3 +...)^2 ))   = lim_(x→0)  (((1/(12))x^4 +O(x^5 ))/(x^4 +O(x^5 ))) = (1/(12))

limx0(ex1)2x2exx2(ex1)2=limx0(1+x+x22+x36+O(x3)1)2x2(1+x+12x2+16x3+O(x3))x2(1+x+12x2+16x3+O(x3)1)2=limx0x+12x2+16x3+...(x2+x3+12x4+16x5+...)x2(x+12x2+16x3+...)2=limx0112x4+O(x5)x4+O(x5)=112

Terms of Service

Privacy Policy

Contact: info@tinkutara.com